Static Dielectric Constant of β-Ga2O3 Perpendicular to the Principal Planes (100), (010), and (001). (1st January 2019) - Fiedler, A.; Schewski, R.; Galazka, Z.; Irmscher, K.
Abstract : The relative static dielectric constant ɛ r of β -Ga2 O3 perpendicular to the planes (100), (010), and (001) is determined in the temperature range from 25 K to 500 K by measuring the AC capacitance of correspondingly oriented plate capacitor structures using test frequencies of up to 1 MHz. This allows a direct quantification of the static dielectric constant and a unique direction assignment of the obtained values. At room temperature, ɛ r perpendicular to the planes (100), (010), and (001) amounts to 10.2 ± 0.2, 10.87 ± 0.08, and 12.4 ± 0.4, respectively, which clearly evidence the anisotropy expected for β -Ga2 O3 due to its monoclinic crystal structure. An increase of ɛ r by about 0.5 with increasing temperature from 25 K to 450 K was found for all orientations. Our ɛ r data resolve the inconsistencies in the previously available literature data with regard to absolute values and their directional assignment and therefore provide a reliable basis for the simulation and design of devices.